'This job is not part of my dreams, what do I leave my children? Nothing'. Livelihoods of Durban car guards at ticketed pay to park sites. (August 2022) - Foster, John RW; Chasomeris, Mihalis; Blaauw, Derick
Car guards are found at many sites where motorists park, including at ticketed pay to park sites. Logic would dictate that most motorists would be less willing to tip car guards when already paying for parking. The study interviewed 15 car guards at different ticketed parking sites in Durban. Their demographic characteristics, among other factors were explored. The findings of this study are then presented and compared to the findings pertaining to an additional 30 car guards (also interviewed in 2019) at free to park sites. Car guards at free to park shopping centres work an average of 44.8 h weekly earning an average of ZAR13 hourly. At ticketed parking shopping centres, they work an average of 63.2 h weekly earning an average of ZAR9.50 hourly. At beachfront free to park sites they work an average of 51.2 h weekly earning an average of ZAR19.10 hourly. At ticketed parking beach front sites, they work an average of 65.7 h weekly earning an average of ZAR7.90 hourly. The study revealed that car guards at ticketed parking sites earn less. However, they remain optimistic, and display a level of entrepreneurship, even in the face of daily bay fees, regulations and ticketed parking.